Seed heteromorphy influences seed longevity in Aegilops. Issue 4 (16th October 2018) - Guzzon, Filippo; Orsenigo, Simone; Gianella, Maraeva; Müller, Jonas V.; Vagge, Ilda; Rossi, Graziano; Mondoni, Andrea
Abstract: The genus Aegilops belongs to the secondary gene pool of wheat and has great importance for wheat cultivar improvement. As a genus with only annual species, regeneration from seeds in Aegilops is crucial. In several species in Aegilops, spikes produce different seed morphs, both in size and germination patterns. However, little is known about the ecology of seed germination, nor about the seed longevity in this genus. Here we investigated the germination phenology of Ae. neglecta under laboratory and field conditions and assessed longevity of different seed morphs of five additional Aegilops species using controlled ageing tests. Large seeds were short-lived and germinated faster than small seeds in most of the species. Field experiments with Ae. neglecta showed that large seeds of the dimorphic pair germinated 3 months after dispersal in contrast to 14 months for smaller seeds. Differences in longevity were detected not only in dimorphic seed pairs, but also among seeds from different positions on the spike. Our results indicate that different longevities in seed morphs of Aegilops may reflect a different soil seed bank persistence, with smaller seeds able to maintain a higher viability after dispersal than larger ones, thereby spreading seedling emergence over two years. Differences of seed germination and longevities between seed morphs in Aegilops may have important implications for ex situ seed conservation and reinforce the hypothesis of a bet-hedging strategy in the germination ecology of this genus.